Pengaruh Preferensi Konsumen Terhadap Keputusan Pembelian (Studi Kasus pada Coffee Shop ALEGRA di Villa Nusa Indah) - Rifaldi, Muhammad Faisal; Santoso, Sugeng; Ardiyansah, Ardiyansah (PANDITA: Interdisciplinary Journal of Public Affairs, 2024)
This study aims to determine and explain the influence of consumer preferences on consumer purchase decisions at ALEGRA coffee shop, both partially and simultaneously. The research method used in this study is a quantitative method with a sample size of 100 respondents. The data collection technique used in this study is questionnaire distribution. The data analysis methods used are validation test, reliability test, classical assumption test, simple linear regression analysis, coefficient of determination analysis, and hypothesis testing. The results of the study show that consumer preferences are categorized as good with an average score of 4.19, purchase decisions are categorized as good with an average score of 4.16, and there is a positive and significant influence of 63% of pricing on purchase decisions at ALEGRA coffee shop in Villa Nusa Indah 2, while 37% is influenced by other factors.